Growing-city pollution and sanitation: causality and evidence from major cities of southwestern Nigeria - Apata, Temidayo Gabriel; Ogunjimi, Sunday Idowu; Okanlawon, Mobolaji Morenike; Bamigboye, Oluwaseun; Adara, Christopher; Egbunonu, Chinwe (Revista Brasileira de Gestão Urbana, 2019)
Growing-city pollution is seen as an inability of an existence infrastructural facilities to support the growing population of humans or other living species in that environment. Growing-city pollution amidst the world has become a topic of increased scholarly review. Yet, insignificant attention has been given to how rising city-pollution influences public health and standard of living. This paper examines the link between growing-city pollution and sanitation. Analysis uses cross-sectional data to examine this causality using an evidence of high populated cities in Southwest, Nigeria. About 6.2% uses modern toilet facilities and about 67% practises open defecation. Access to water/sanitation facilities, distance to nearest health clinic or hospital are the main features influencing multidimensional poor sanitation/hygiene index. Focus Group Discussions (FGDs) revealed that discussants lacked an understanding of the linkages between hygiene practices and water-related diseases. Growing-city pollution influences endemic chronic diseases because sanitation is poorly accessible. Interaction between sanitation and population density in predicting poor health outcomes as evidenced in this study. Efforts should be geared by all stakeholders to boost and create livelihoods activities that can curtail rural-urban drift. Rural migrants should be encourage to stay in their vicinity to enjoy less air-polluted environment and decent accommodation.